Financial Statement Quality, Corporate Social Responsibility, and Firm Value: A Review of Miles and Snow’s Business Strategy Typology - Abdul Malik Kumar; Harmono Harmono (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2026)
Introduction/Main Objectives: This study investigates the strategy-contingent effects of financial reporting quality and corporate social responsibility (CSR) on firm value during the Covid-19 crisis. Background Problems: The pandemic and large-scale social restrictions in Indonesia heightened market uncertainty, raising questions about the relative importance of financial versus non-financial information across different business strategies. Research methods: Using purposive sampling, this study analyzes 254 manufacturing firms listed on the Indonesia Stock Exchange during 2019–2021. Business strategies are classified using factor analysis, followed by strategy-based regression testing. Findings/Results: Financial reporting quality positively influences firm value for both prospector and defender firms. CSR shows no significant effect for prospector firms and a negative effect for defender firms. Conclusion: The value relevance of disclosures is strategy-dependent, with financial reporting quality playing a dominant role during periods of extreme uncertainty.